Fa’āliyah Ṭarīqah al-Sam’iyyah al-Syafahiyyah Mundamijah bi-Renderforest al-Qāim ‘alā al-Żakāi al-Iṣṭinā’ī li-Ta’līm al-Istimā’ ladai Ṭullāb al-Madrasah al-‘Āliyah - Aisyah, Maulida Nur; Inayah, Inayah; Setiawan, Akhmad Yusuf Isnan; Waemamu, Waesama-ae (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the effectiveness of the audiolingual method integrated with Renderforest, an artificial intelligence-based platform, in improving the Arabic listening skills of grade X students at MAN 2 Kota Semarang. This quantitative study employed a quasi-experimental design with a non-equivalent control group, comprising two classes of 35 students each, serving as the experimental and control groups. Data were collected through observation and pretest–posttest instruments consisting of 50 multiple-choice questions, analyzed using SPSS 25. The independent sample t-test results showed that the calculated t-value was 1.857, while the table t-value was 1.667. The calculated t-value was greater than the table t-value, indicating a statistically significant difference between students taught using the audiolingual method with Renderforest and those taught without it. The use of Renderforest as an audiovisual medium effectively increased student motivation, participation, and engagement during listening activities. This study concludes that combining the classic audiolingual approach with modern AI-based media is pedagogically relevant and improves students' affective and motivational aspects. Therefore, it is recommended to conduct further research by applying this integration in longer learning durations and higher exercise intensities to optimize its effectiveness in teaching Arabic listening.